Extracellular vesicles from amniotic fluid, milk, saliva, and urine expose complexes of tissue factor and activated factor VII. (29th July 2022) - Hu, Yong; Repa, Andreas; Lisman, Ton; Yerlikaya‐Schatten, Guelen; Hau, Chi; Pabinger, Ingrid; Ay, Cihan; Nieuwland, Rienk; Thaler, Johannes
Abstract: Background: Tissue factor (TF) is expressed in the adventitia of the vessel wall and on extracellular vesicles (EVs) in body fluids. TF and activated coagulation factor (F) VII(a) together form the so‐called extrinsic tenase complex, which initiates coagulation. Aim: We investigated whether EVs in amniotic fluid, milk, saliva, and urine expose functional extrinsic tenase complexes that can trigger coagulation. Methods: Milk, saliva, and urine were collected from healthy breastfeeding women ( n = 6), and amniotic fluid was collected from healthy women undergoing routine amniocentesis ( n = 7). EVs were isolated from body fluids by size exclusion chromatography (SEC) and clotting experiments were performed in the presence and absence of antibodies against TF and FVIIa in normal plasma and in FVII‐deficient plasma. The ability of body fluids to generate FXa also was determined. Results: Amniotic fluid, milk, saliva, and urine triggered clotting of normal plasma and of FVII‐deficient plasma, which was almost completely inhibited by an anti‐FVII antibody and to a lesser extent by an anti‐TF antibody. Fractionation of body fluids by SEC showed that only the fractions containing EVs triggered clotting in normal plasma and FVII‐deficient plasma and generated FXa, which again was almost completely inhibited by an anti‐FVII antibody and partially by an anti‐TF antibody. Conclusion: Here we show that EVs from amniotic fluid, milk, saliva, and urine expose complexes of TF and FVIIa (i.e., extrinsic tenase complexes) that directly activate FX. Based on our present findings we propose that these EVs from normal body fluids provide hemostatic protection.